1984
DOI: 10.1002/chin.198436233
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: REACTION OF N‐ACYLISATINS WITH DIAMINES

Abstract: Bei der Umsetzung der Acylisatine (I) mit den Phenylendiaminen (II) entstehen die Chinoxalinone (III), die zum Teil zu (IV) acylien werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, it has been reported that with the latter two solvents a spiro benzimidazole derivative is also formed 330 . The formation of ring opened products has also been reported to occur when using alkyldiamines 331 (Scheme 79). Likewise, the reactions of 1-acylisatins and anilines 296 or N-methylanilines 332 led to ring opened products, but one report states that 4-arylthio and 4-arylsulfonylanilines react with 1-acetylisatin to furnish 3-imines 333 .…”
Section: Scheme 76mentioning
confidence: 96%
“…However, it has been reported that with the latter two solvents a spiro benzimidazole derivative is also formed 330 . The formation of ring opened products has also been reported to occur when using alkyldiamines 331 (Scheme 79). Likewise, the reactions of 1-acylisatins and anilines 296 or N-methylanilines 332 led to ring opened products, but one report states that 4-arylthio and 4-arylsulfonylanilines react with 1-acetylisatin to furnish 3-imines 333 .…”
Section: Scheme 76mentioning
confidence: 96%
“…The Schiff bases (a) and (b) (Scheme 1) derived from isatin and its derivatives with different amines have been studied [1, 2, 6, 813]. The reaction of N-acetyl, N-benzoyl, and N-tosylisatin and their Schiff base derivatives (c) and (d) (Scheme 1) with ethanol, methanol, isopropyl alcohol, allyl alcohol, TsNH 2 , pyrrolidine, and water yield products resulting from nucleophilic attack at the C-2 carbonyl that leads to heterocyclic ring cleavage [8, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Isatin (indole-2,3-dione) and its derivatives have shown a wide scale of biological activities such as antibacterial [ 1 – 3 ], antifungal [ 1 , 3 – 5 ], anticonvulsant [ 2 , 6 ], anti-HIV [ 7 ], anticancer [ 1 , 2 ], antiviral [ 1 ], and enzyme inhibitors [ 2 ]. The Schiff bases (a) and (b) ( Scheme 1 ) derived from isatin and its derivatives with different amines have been studied [ 1 , 2 , 6 , 8 13 ]. The reaction of N-acetyl, N-benzoyl, and N-tosylisatin and their Schiff base derivatives (c) and (d) ( Scheme 1 ) with ethanol, methanol, isopropyl alcohol, allyl alcohol, TsNH 2 , pyrrolidine, and water yield products resulting from nucleophilic attack at the C-2 carbonyl that leads to heterocyclic ring cleavage [ 8 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The Schiff bases and spiro-thiadiazoline derivatives of isatins have shown remarkable biological activities. 7,8 Therefore, design and consequent synthesis of such lactam based compounds as drugs candidates have been receiving a considerable attention in the field of medicinal organic chemistry. 9,10 The introduction of fluorine in heterocycles is known to modify the course of the reaction beside influencing the biological activity.…”
Section: Introductionmentioning
confidence: 99%